Rome and the Colonial City Rethinking the Grid - Greaves, Sofia; Wallace-Hadrill, Andrew (Oxbow Books, 2022)
According to one narrative, that received almost canonical status a century ago with Francis Haverfield, the orthogonal grid was the most important development of ancient town planning, embodying values of civilization in contrast to barbarism, diffused in particular by hundreds of Roman colonial foundations, and its main legacy to subsequent urban development was the model of the grid city, spread across the New World in new colonial cities. This book explores the shortcomings of that all too colonialist narrative and offers new perspectives. It explores the ideals articulated both by ancient city founders and their modern successors; it looks at new evidence for Roman colonial foundations to reassess their aims; and it looks at the many ways post-Roman urbanism looked back to the Roman model with a constant re-appropriation of the idea of the Roman.